Workplace Spirituality And Its Impact On Organizational Commitment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Spirituality has always been an important part of our lives, and it is today regarded as one of the most influential factors in the advancement of educational institutions and, therefore, an academic's professional life. Workplace spirituality isn't about instilling optimism or persuading others to adopt a specific religion. It does not always mean a connection to a certain religious practise, but it does. Spirit at work is a philosophy that describes the experiences of teachers who are enthused and energised by their work, who find meaning and inspiration in their work, who can express their true self, and who feel they are connected to those with whom they work. In the Chennai district, the majority of teachers in government-aided higher educational institutions have a moderate standard of occupational spirt. The current analysis is limited to only two correlates of occupational spirituality, namely job satisfaction and organisational engagement..